Therapeutic Effect of a Polyherbal Unani formulation in Sayalan al-Rahim (Abnormal vaginal discharge) - A clinical study (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Sayalan al-Rahim (abnormal vaginal discharge) is one of the very common female complaints encountered in daily practice. It is an important public health problem in India and can occur mostly due to sexually and non-sexually transmitted infections. A clinical trial was conducted in the Department of Ilmul Qabalat wa Amraze Niswan, NIUM, Bengaluru. 30 patients of Sayalan al-Rahim were included in the study after obtaining their informed consents. All the patients were clinically assessed and diagnosed on the basis of thorough history, presence of abnormal vaginal discharge and other associated symptoms. Then, polyherbal Unani formulation was administered orally 5 gm twice daily with water from 5th day of menses for 21 days. The severity of disease and efficacy of treatment was assessed on the basis of subjective and objective parameters. Clinical improvement of 70% in Sayalan al-Rahim was observed. Mean ± SD of vaginal discharge before and after treatment was 2.87 ± 0.35 and 0.37 ± 0.61, VSS scale before and after treatment was 23.53 ± 3.49 and 10.33 ± 4.05 and VAS scale for LBA and LAP before and after treatment were 6.37 ± 2.36 to 2.37 ± 1.87 and 2.43 ± 1.96 to 0.03 ± 0.18, respectively with p=< 0.001** considered strongly significant. Polyherbal unani formulation was found safe and effective in improving the sign and symptoms of Sayalan al-Rahim. It was concluded that polyherbal Unani formulation can be used safely and effectively for the treatment of Sayalan al-Rahim.